(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
This article is the study of school-going age children which is now a fundamental right in Nepal as described in article-31 in the constitution of Nepal in 2015 and the Right to Free and Compulsory Education Act, 2018. On the same foundation, this article aims to study the view of parents towards the national policy of free and compulsory education. The research is based on the qualitative research design, which includes an in-depth study and document review of different national policies and field studies. Furthermore, the field study was conducted among the parents using a questionnaire interview to determine the real and exact situation of parents towards free and compulsory education. The research findings depicted no real feeling of free and compulsory education at the grassroots level. Parents have to pay some amount of money even in the community school for the education of their children. The scholarships provided by the nation are not sufficient for the poor, indigenous, backward and physically and mentally disabled students. The three-tier government has to work at its best to bring free and compulsory education into real practice in our everyday lives. The stakeholders are responsible for bringing this into practice as education is the only way to a prosperous and happy society and nation.